Teaching of social studies : a practical approach - Aggarwal, J. C. (New Delhi : Vikas Publishing House, 2007)
Teaching of Social Studies is written for the BEd students of different universities in India. It has also been found equally useful in the Middle-east and South-east Asian countries on account of its wide coverage. The teaching of social studies is of great significance in the building of a great nation. The book, therefore, focuses on the ideals, values and forces shaping the society. It has been specially designed to equip the prospective teacher with maximum knowledge and information needed for a brilliant success in the examination. Twenty-eight suggestive lesson plans have been given especially for their guidance. The revised edition is in accordance with the latest Model Syllabus for BEd formulated by the UGC. It also takes note of the modifications by a number of universities in the UGC Syllabus, as well as the guidelines issued by the NCERT. Syllabi prescribed by the CBSE and the Inter-State Board for Anglo-Indian Education have also been taken into consideration. Every possible effort has been made to incorporate the latest material on the subject. A new chapter on (3z(BTeaching Aids: Maps, Figures and Tables(3y (Bhas been added to provide assistance and guidance to the students in this area. There is also a Quiz to heighten the motivation of the learners. The book will prove very useful to all those who are engaged in improving the teaching of Social Studies.s
Keywords: Social sciences -- Study and teaching (Secondary).; Teaching social studies